Mystery of gamma wave stimulation in brain disorders - Qianting Deng; Chongyun Wu; Emily Parker; Jing Zhu; Timon Cheng-Yi Liu; Rui Duan; Luodan Yang (Molecular Neurodegeneration)
Abstract Neuronal oscillations refer to rhythmic and periodic fluctuations of electrical activity in the central nervous system that arise from the cellular properties of diverse neuronal populations and their interactions. Specifically, gamma oscillations play a crucial role in governing the connectivity between distinct brain regions, which are essential in perception, motor control, memory, and emotions. In this context, we recapitulate various current stimulation methods to induce gamma entrainment. These methods include sensory stimulation, optogenetic modulation, photobiomodulation, and transcranial electrical or magnetic stimulation. Simultaneously, we explore the association between abnormal gamma oscillations and central nervous system disorders such as Alzheimer’s disease, Parkinson’s disease, stroke, schizophrenia, and autism spectrum disorders. Evidence suggests that gamma entrainment-inducing stimulation methods offer notable neuroprotection, although somewhat controversial. This review comprehensively discusses the functional role of gamma oscillations in higher-order brain activities from both physiological and pathological perspectives, emphasizing gamma entrainment as a potential therapeutic approach for neuropsychiatric disorders. Additionally, we discuss future opportunities and challenges in implementing such strategies.